Heterogeneous reactions of mineral dust aerosol: implications for tropospheric oxidation capacity - Tang, M. J.; Huang, X.; Lu, K. D.; Ge, M. F.; Li, Y. J.; Cheng, P.; T. Zhu; Ding, A. J.; Zhang, Y. H.; Gligorovski, S.; Song, W.; X Ding; et al. (Atmospheric Chemistry and PhysicsAtmospheric Chemistry and PhysicsAtmospheric Chemistry and Physics, 2017)
Heterogeneous reactions of mineral dust aerosol with trace gases in the atmosphere could directly and indirectly affect tropospheric oxidation capacity, in addition to aerosol composition and physicochemical properties. In this article we provide a comprehensive and critical review of laboratory studies of heterogeneous uptake of OH, NO3, O-3, and their directly related species as well (including HO2, H2O2, HCHO, HONO, and N2O5) by mineral dust particles. The atmospheric importance of heterogeneous uptake as sinks for these species is assessed (i) by comparing their lifetimes with respect to heterogeneous reactions with mineral dust to lifetimes with respect to other major loss processes and (ii) by discussing relevant field and modeling studies. We have also outlined major open questions and challenges in laboratory studies of heterogeneous uptake by mineral dust and discussed research strategies to address them in order to better understand the effects of heterogeneous reactions with mineral dust on tropospheric oxidation capacity.
Keywords: arizona test dust; calcium-carbonate particles; gas-particle interactions; gaseous-hydrogen peroxide; individual atmospheric particles; knudsen cell reactor; pearl river delta; phase diffusion-coefficients; total oh reactivity; volatile organic-compounds